2013
DOI: 10.1038/bjc.2013.519
|View full text |Cite
|
Sign up to set email alerts
|

hr-HPV testing in the follow-up of women with cytological abnormalities and negative colposcopy

Abstract: Background:The follow-up after abnormal Pap smear and negative colposcopy is not clearly defined. This study aimed at investigating the role of hr-HPV testing in the management of abnormal Pap test and negative colposcopy for Cervical Intraepithelial Neoplasia grade 2 or worse (CIN2+).Methods:The study enroled 1029 women with abnormal screening cytology (years 2006–2010) and negative colposcopy for CIN2+, which subsequently performed a hr-HPV test. Incident CIN2+ lesions were identified through linkage with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Overall, consistent with the presence of BV-associated microbiomes, a high concentration of pro-inflammatory cytokines was detected in the vaginal environment of CIN patients, including IL1a, IL1b, IL6, IL8, and TNFa, with the highest values found in the CST-IV profile compared to the others, confirming that BV-like vaginal microbiomes are associated with increased local inflammation (Campisciano et al, 2018;De Seta et al, 2019;Torcia, 2019).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, consistent with the presence of BV-associated microbiomes, a high concentration of pro-inflammatory cytokines was detected in the vaginal environment of CIN patients, including IL1a, IL1b, IL6, IL8, and TNFa, with the highest values found in the CST-IV profile compared to the others, confirming that BV-like vaginal microbiomes are associated with increased local inflammation (Campisciano et al, 2018;De Seta et al, 2019;Torcia, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…HPV status was determined by Cobas 4800 HPV Test (Roche Diagnostics, Monza, Italy), allowing detection of 18,31,33,35,39,45,51,52,56,58,59,66,68. Patients were followed according to the Regional Protocol for CC prevention (Carozzi et al, 2015) and LEEP by monopolar energy diathermic loop was used for lesion removal. The protocol includes PAPtest, colposcopy and hrHPV-test before LEEP and follow-up control at 6 months after lesion removal.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…However, most of the studies showed that HPV prevalence decreases with increasing age with a peak prevalence in younger women 28 . Carozzi et al reported in their study from Italy, that HR‐HPV positivity was higher in patients younger than 35 years of age (62.9%) than patients older than 35 (54.7%) 29 . In the study of Hashim et al, HR‐HPV positivity rates in two age groups (34–43, 44–69) were close, however, the older age group had a slightly higher number 30 .…”
Section: Discussionmentioning
confidence: 95%
“…Nowadays, numerous assays have been developed to detect nucleic acids of oncogenic and nononcogenic HPVs in cervical samples. The main advantage of using HPV testing is the high sensitivity, with a consequent high negative predictive value, since the absence of carcinogenic HPV indicates an extremely low risk of cervical intraepithelial neoplasia grade 3 (CIN3) or cancer [ 20 22 ], and the longer protection compared with cytology, since the risk of CIN3 and cancer remains very low up to 5 years after a negative HPV test [ 23 ]. The only concern is the low specificity of the HPV assays due to the fact that they cannot discriminate between transient and persistent HPV infections.…”
Section: Hpv Dna Rna and Proteins As Biomarkers For Cervical Neomentioning
confidence: 99%